2010
DOI: 10.1016/j.compscitech.2010.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Study on interfacial adhesion strength of single glass fibre/polypropylene model composites by altering the nature of the surface of sized glass fibres

Abstract: Polypropylene (PP) compatibly sized glass fibres (GFs) were treated with boiling water and toluene, respectively, to reveal the interactions of water and toluene with different components in the sizing of sized GF and their influences on the interfacial adhesion strength of GF/PP model composites.Compared to control GF/PP model composites, about 30% increase of interfacial adhesion strength was achieved for composites with water-treated GF, whereas a small decrease of interfacial adhesion strength was revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…A further increase of the silane content did not result in enhanced composite strength, the values are comparable to those at 1.5 wt% silane, however, the estimated response surface indicates maximum composite strengths between 1.5 and 3 wt% silane. This is related to the parabolic fitting of the estimated surface, although it has been reported that excess silane results in an increased build-up of physisorbed silane layers which can lower the interfacial strength [10,35]. Regarding the film former, at all silane contents investigated a slight increase of the transverse tensile strength with decreasing film former content can be observed ( Figure 1a).…”
Section: Statistical Analysis Of the Factorial Designmentioning
confidence: 99%
See 2 more Smart Citations
“…A further increase of the silane content did not result in enhanced composite strength, the values are comparable to those at 1.5 wt% silane, however, the estimated response surface indicates maximum composite strengths between 1.5 and 3 wt% silane. This is related to the parabolic fitting of the estimated surface, although it has been reported that excess silane results in an increased build-up of physisorbed silane layers which can lower the interfacial strength [10,35]. Regarding the film former, at all silane contents investigated a slight increase of the transverse tensile strength with decreasing film former content can be observed ( Figure 1a).…”
Section: Statistical Analysis Of the Factorial Designmentioning
confidence: 99%
“…The physical significance of the proposed amount of silane is questionable, since this could be due to the parabolic nature of the model fit. However, it is known that excessive silane in sizings results in an increasing amount of physisorbed silane which can deteriorate the composite properties [10,35]. Figure 3 shows SEM micrographs of fractured surfaces of the composites with different sizing formulations after compression shear testing.…”
Section: Effect Of Sizing Formulation and Glass Fibre Diameter On Thementioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of NaBF 4 , the protonation of amine groups is mainly attributed to the intramolecular and intermolecular interactions between amino groups and silanol groups as well as the interaction between amino groups and environmental carbonic acid [15,31,32]. The increase in N-2 at% of sized GFs with NaBF 4 confirms the presence of NaBF 4 in sized GF surfaces, since BF 4 has high association constant and hydrophobicity, which are in favor of the formation of BF 4 /N + associations [33,34].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, stress can be efficiently transferred from matrix to load bearing reinforcing fibres leading to GF/PP composites with great performance. Besides these perfect covalent bondings, there are still some un-reacted silanol groups, polar groups of lubricants or surfactants [15] and other weak points in the interphase, which are liable to interact with [16] and accommodate water molecules, leading to the degradation of interphase properties, correspondingly, the mechanical properties of composites. When the non-hygroscopic features of GFs and PP are taken into consideration [17], it becomes obvious that proper interphase design holds great promise to improve the hygrothermal durability of composites [3].…”
Section: Introduction -2 -mentioning
confidence: 99%